Elaboración de una guía para laboratorios de la materia de telefonía de la escuela de tecnologías en la Universidad de las Américas - Quiroz Fuel, Jorge Luis (2015)
The making of this Project has as a main objective to make four lab practices in the field of Telephony Career Networking and Telecommunications, which will be used as a document to support for students who take this course. The preparation of this documentary work will be established through research needed for each practice in order to contain reliable and relevant information which will feature the same supervision and support of teachers assigned by the University of the Americas to evaluate the content of this document. The expected range for the preparation of this work will be determined by the results that students obtain in the assessments of the worksheets labs practices.